STUDI PERTUMBUHAN DAN HASIL DUA VARIETAS KENTANG (Solanum tuberosum L.) PADA PEMBERIAN SUMBER PUPUK NITROGEN YANG BERBEDA - dardiansyah dardiansyah; Anis Rosyidah; Siti Muslikah (AGRONISMA, 2021)
Potato (Solanum tuberosum L.) is one of the important commodities, because it is a source of carbohydrates that is in great demand by the public and has high commercial value.  This increase in potato demand indicates that potato production needs to be increased. Growth and yield of potato plants are not only influenced by genetic factors but also environmental factors.  Environmental factors influence, including the use of inappropriate fertilizers or nitrogen fertilizers required in high quantities.  Currently, farmers use more urea fertilizer because of its higher N content, but alternative sources of nitrogen are other.  This study aims to get the right one to increase the growth and yield of potato tubers and varieties. The research was conducted from July to October 2020 in Sumberejo village, Batu with an altitude = 690 m above sea level, an average temperature of 21 °C, 89% humidity and clay textured soil.  The research was conducted experimentally using a factorial Randomized Block Design (RAK) consisting of two factors, namely: the first factor was the source of N which consisted of 2 levels, namely Si = Urea and S2 = Ammonium Nitrate.  the second factor of potato plant varieties consisting of 2 levels.  vaitu V1 = Median and V2 = Atlantic.  Each treatment was repeated six times from each replication consisting of three samples.The results showed that the combination of ammonium nitrate and Atlantic varieties gave better potato growth and yield compared to other treatments on the variables of plant height, stem diameter and number of leaves at the age of 21, 61 and 71, respectively, the highest yields were obtained with ammonium nitrate treatment  resulted in a stem diameter of 11.21 (mm) with a plant height of 19.41 cm and the number of leaves 174.83 strands.  In the leaf area parameter, the number of stems for each treatment gave results that did not significantly affect each age of observation.  The combination of urea treatment with Medians and Atlantic varieties gave better potato tuber yields with plant weights of 710.88 g and 686.46 g and fresh tuber weights per hectare of 37.52 tons/ha and 36.23 tons/ha.